ANALISIS KINERJA KEUANGAN PT BANK SYARIAH INDONESIA TBK PERIODE 2020-2022 - Izom, Siti; Yanto, Roni; Aziz, Khalid Fauzi (Department of Accounting-Faculty of Economic and Business (FEB), 2023)
This research aims to analyze the financial performance of Bank Syariah Indonesia for the 2020–2022 period. The sample in the research is the annual financial report of PT Bank Syariah Indonesia Tbk regarding financial position, profit and loss, and cash flow reports. The sampling technique uses non-probability-purposive sampling. The research method used in this study is descriptive with a quantitative approach. The data analysis technique used is financial ratio analysis, including liquidity, solvency, and profitability ratios. The results of this research show that the bank's financial performance in terms of liquidity ratios seen from the Cash Asset indicator is in a very healthy condition, but the Loan to Deposit Ratio is in an unhealthy condition because it does not reach the industry standards set by Bank Indonesia. The solvency ratio seen from the capital adequacy ratio indicator is in a very healthy condition. The financial performance of Bank Syariah Indonesia is assessed using the profitability ratio seen from the Return on Assets indicator, which is in a very healthy condition. Judging from the Return on Equity indicator in the 2020 period, it is in a healthy condition, while in the 2021–2022 period, it is in an unhealthy condition.